The contribution of the Anglican Church of Southern Africa to social development in South Africa and its potential role as a national partner in development - Mark, Delene Melissa (Department of Social Development, 2015)
This research investigates the role of the Anglican Church of Southern Africa in social development in South Africa. The hypothesis states that the Church has been involved in social development since its inception and currently contributes significantly to social development in South Africa. Within the context of poverty and the challenges faced by South Africa in alleviating poverty today, the researcher will establish if the Anglican Church could be considered a potential partner in poverty alleviation in South Africa, together with the public and private sectors.